Clinical and Hormonal Profile of Oligomenorrhea in Bhaktapur Hospital - Pandit, Benju (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To analyze the clinical and hormonal profile of patients presenting with oligomenorrhoea in outdoor consultation. Methods: This is an observational descriptive study conducted between January to April 2022 in Bhaktapur Hospital. Data were collected in outpatient clinic of Department of Obstetrics and Gynecology. Descriptive parameters were analyzed. Results: There were 80 patients enrolled in the study. Cause of oligomenorrhoea was identified in only one-third of cases. Common diagnosed cause of oligomenorrhea was Polycystic Ovary Syndrome (16;20%) followed by thyroid disorder (8;10%) and hyperprolactinemia (2;2.5%). Conclusions: The most common identified causes of oligomenorrhea were polycystic ovarian syndrome and thyroid disorder but two-third of cases had no any identifiable cause. Keywords: hyperprolactinemia, oligomenorrhea, PCOS, thyroid disorder